FAKTOR-FAKTOR YANG MEMPENGARUHI KESEJAHTERAAN KELUARGA DI SUMATERA BARAT - Aulia Rizki Akbar; Akhirmen Akhirmen; Mike Triani Triani (Jurnal Ecogen, 2018)
The purpose of this research is to indentified factor-factor that influence the family welfare in West Sumatera. Based on the generic fenomena that happened, the formulation in this research is how the first marriage age, work, education, and health give effected to family welfare in West Sumatera. This research use Sussenas 2016 data, and the research population is household in West Sumatera. Sample that used in this research is ammount to 9455 head of household. The sample has been taking from 19 districts/city that spread in West Sumatera,even if in city or country. This research use the Logistic Model and the hypothesis test that used in this research is Wald test with alpha 5%. Based on the research the first marriage age, work, education, and health have significant effect to the family welfare in West Sumatera.   Keyword :  Family Welfare, First Marriage Age, Work, Education, Health